50 Wikipedia culture and usage: a survey of first year medical students to determine barriers and facilitators. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Walker, Melanie; Murray, Heather; Dawson, Jennifer; Maggio, Lauren
Abstract : Objectives: Wikipedia is the sixth most trafficked website globally and used heavily by individuals seeking health information. For example, Wikipedia's pneumonia entry is, on average, viewed daily over 10 000 times. Unsurprisingly, researchers have identified medical students among Wikipedia users. Medical students are trained to practice evidence-based medicine (EBM) that requires accessing and critically appraising information from a variety of sources. While researchers have investigated use of information resources (e.g., MEDLINE, UpToDate, BMJ Best Practice) as evidence dissemination tools, there is limited information in relation to Wikipedia. This project examined medical student perceptions of Wikipedia use by medical practitioners and the public, and in ongoing student training. Method: In Fall 2017, 101 first-year medical students at Queen's University, Canada participated in a longitudinal project to learn how to contribute to a medical page in Wikipedia. This was part of their critical appraisal, research and lifelong learning course which is a mandatory component of the students' EBM training. Based on their engagement with Wikipedia pages and the Wikipedia community, the students were required to complete a survey at project end that sought their feedback on: (1) whether and how the project changed their opinion of Wikipedia as a medical resource for the public; (2) their views on Wikipedia as a resource for medical practitioners, and (3) their prediction on future Wikipedia usage going forward in medical school or as a resident. Two members of the research team who were not involved in marking student assessments reviewed survey responses and, using thematic analysis, identified salient themes. Results: Students recognised Wikipedia as a useful health information resource for the public. Students also described an increased appreciation of the Wikipedia editing and citation process and assurance with the oversight and engagement provided by the Wikipedia community. Conversely, perceived barriers to recommending Wikipedia to the public included concerns about Wikipedia editors' lack of content expertise, unreliability of information and outdated information compared with other evidence-based resources. With respect to their opinion of Wikipedia as a resource for medical practitioners, student opinions were more divided with concerns raised regarding the depth, comprehensiveness and reliability/accuracy of information provided compared to other resources. However, despite these reservations, the large majority of respondents indicated they will use Wikipedia going forward in medical school and as a resident. Students attributed Wikipedia's utility to its' ease of access, usefulness as a 'refresher' on background information and its use as a springboard to more evidence-based resources. Conclusions: Medical students reported appreciation for Wikipedia as a useful health information resource given their enhanced understanding of the editing and oversight processes. Students cited Wikipedia as a resource they would recommend to the public and that they will continue to use owing to its ease and speed of access to background information on health topics. Concerns about reliability, accuracy and currency of information were barriers identified in recommending Wikipedia to medical practitioners. There is an opportunity for medical schools and educators to develop a health advocacy partnership with the Wikipedia community to improve evidence-based content.